SAVING BEHAVIOR OF KAZAKHSTANIS: DRIVING PATTERNS AND CHALLENGES - Sharypkhanova, Kamila; Altynbayev, Bissultan; Darmentayeva, Albina (Nazarbayev University Graduate School of Public Policy, 2022)
This study assesses the saving behavior of Kazakhstanis, particularly, the main attention is paid to the major demographic factors that drive people to save and challenges people experience to save, especially in conditions of socio-economic instability. Age, education level, income and family status were chosen as key factors that may have a significant impact on the person’s financial planning. The authors of this research define saving as a certain part of income that goes to the future consumption in case of unexpected events. Data were collected using a self-administered questionnaire from 193 respondents across Kazakhstan as well as five semi-structured interviews with the experts in the sphere of finance and financial education. The findings showed that income and the level of education have a greater influence on the propensity to save, whereas age and marital status have shown controversial results. The research outcome also demonstrates that consistent saving behavior is constrained by low income, the insufficient level of financial literacy, the existence of consumer loans, and increasing inflation that devalue people’s savings.
Keywords: Type of access: Gated Access; socio-economic instability; saving behavior of Kazakhstanis